2023
DOI: 10.3390/antiox12051111
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Biosynthesis of Antioxidant-Active Metabolites in In Vitro Cultures of Isatis tinctoria (Brassicaceae) by Biotechnological Methods/Elicitation and Precursor Feeding

Abstract: This study aimed to establish the in vitro shoot culture of Isatis tinctoria L. and its ability to produce antioxidant bioactive compounds. The Murashige and Skoog (MS) medium variants, containing different concentrations (0.1–2.0 mg/L) of benzylaminopurine (BAP) and 1-naphthaleneacetic acid (NAA) were tested. Their influence on the growth of biomass, accumulation of phenolic compounds, and antioxidant potential was evaluated. To improve the phenolic content, agitated cultures (MS 1.0/1.0 mg/L BAP/NAA) were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Phenolic compounds are well known to have antioxidant activity [40][41][42][43][44][45]. The antioxidant capacity of the studied four bilberry extracts was measured by FRAP, CUPRAC and DPPH methods.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds are well known to have antioxidant activity [40][41][42][43][44][45]. The antioxidant capacity of the studied four bilberry extracts was measured by FRAP, CUPRAC and DPPH methods.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…As a result of the evaluation of the studies, it was observed that there was a direct correlation between the anthocyanin content of the extracts and the antioxidant capacity values of the CUPRAC method (Figure 4). Phenolic compounds are well known to have antioxidant activity [40][41][42][43][44][45]. The antioxidant capacity of the studied four bilberry extracts was measured by FRAP, CUPRAC and DPPH methods.…”
Section: Antioxidant Activitymentioning
confidence: 99%